Auditor-provided tax services and tax avoidance: evidence from Spain. Issue 1 (2nd January 2021) - Garcia-Blandon, Josep; Argiles-Bosch, Josep Maria; Ravenda, Diego; Castillo-Merino, David
ABSTRACT: We investigate the relationship between auditor-provided tax services (APTS) and tax avoidance in Spain. As a result of a recently enacted EU legislation, APTS is seriously restricted within the EU. The evidence available so far for the US provides consistent support for a positive relationship between APTS and tax avoidance. However, given the importance of country-specific institutional issues, such as litigation risk, to understand the relationship between auditors and clients, the possibility of generalising the US evidence to other countries is limited. Supporting this view, our results indicate that the positive relationship between APTS and tax avoidance observed in the US does not hold in the Spanish market. This result seems robust, as it holds independently of the proxy utilised for measuring tax avoidance, as well as across an array of sensitivity checks. This study has potentially interesting implications at both theoretical and practical levels.